Seven-coordinate iron(II) complexes of sulfur-based N3S2-macrocyclic ligands: synthesis, properties, and crystal structure - Shaban, Shaban Abd El Fattah Youssef; Ibrahim, Mohamed M.; Heinemann, Frank Wilhelm; van Eldik, Rudi (Journal of Coordination Chemistry, 2012)
The reaction of pyridine-2,6-dicarbaldehyde or 2,6-diacetylpyridine with 1,2-bis(o-aminophenylthio) ethane (1) in acetonitrile in the presence of stoichiometric amounts of iron(II) perchlorate gave the complexes [(pyN(3)S(2))Fe-II(ClO4)(2)] (4) and [(pyN(3)Me(2)S(2)) Fe-II(ClO4)(2)] (5) of the 15-membered N3S2 macrocyclic ligands, pyN(3)S(2) = 6,7-dihydro-15,19-nitrilobenzo( e,p)(1,4,7,15)dithiadiazacyclo-heptadecine-N, N', N '', S, S' and pyN(3)Me(2)S(2) = 6,7-dihydro- 16,18-dimethyl-15,19-nitrilobenzo(e,p)(1,4,7,15)dithiadiazacyclo-heptadecine-N, N', N '', S, S', respectively. Physical measurements led to the conclusion that these complexes contained seven-coordinate iron(II) and a single-crystal X-ray examination of 4 confirmed this. Coordination of the Fe(II) center in 4 is best described as distorted pentagonal-bipyramidal with the three nitrogen atoms and two sulfur donors of the macrocycle defining the pentagonal plane and the perchlorate ions occupying axial positions. Room temperature (293 K) magnetic moments of 4 and 5 (mu(eff) = 4.9 and 4.7 B.M., respectively) are close to the value predicted for high-spin d(6) systems.
Keywords: Iron(II) complexes; Seven-coordinate; Macrocyclic ligands; Pentagonal-bipyramidal